1998
DOI: 10.1046/j.1365-2885.1998.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and pathophysiological modulation of food intake and forestomach motility in small ruminants

Abstract: I Introduction II Pharmacological modulation of food intake and forestomach motility II 1. Orexigenic agents 1.1 glutamate 1.2 benzodiazepines 1.3 opioid receptor agonists and antagonists 4 neuropepetides Y (NPY) II 2. Anorectic agents 2.1 cholecystokinin (CCK) agonists and antagonists 2.2 serotonin receptor agonists and antagonists 2.3 dopamine receptor agonists and antagonists 2.4 alpha‐2 adrenoceptor agonists and antagonists III Anorexia and ruminal stasis during the Acute Phase Response to infections 1. cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 162 publications
(293 reference statements)
0
4
0
Order By: Relevance
“…The authors concluded that 5‐HT 1 , 5‐HT 2 , 5‐HT 3 , and 5‐HT 4 receptors were all involved in regulation of the small intestinal migrating myoelectric complex (MMC) and on forestomach hypomotility occasionally recorded concomitantly to duodenal phase III activity. In goats, however, the 5‐HT 1 receptor agonist MDL‐72832 increased the rumen contraction rates (van Miert & van Duin, 1998). In a subsequent study, Plaza et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that 5‐HT 1 , 5‐HT 2 , 5‐HT 3 , and 5‐HT 4 receptors were all involved in regulation of the small intestinal migrating myoelectric complex (MMC) and on forestomach hypomotility occasionally recorded concomitantly to duodenal phase III activity. In goats, however, the 5‐HT 1 receptor agonist MDL‐72832 increased the rumen contraction rates (van Miert & van Duin, 1998). In a subsequent study, Plaza et al.…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggest that in sheep, 5‐HT 4 receptor‐agonists act peripherally and are excitatory, while 5‐HT 3 agonists act centrally and are inhibitory. In goats, however, the peripheral 5‐HT 4 receptor agonist 5‐methoxytryptamine decreased rumen contraction rates (van Miert & van Duin, 1998). The literature demonstrating the involvement of 5‐HT receptors in abomasal motility and/or abomasal displacement in cattle is not available.…”
Section: Introductionmentioning
confidence: 99%
“…The reported results with specific agonists and antagonists suggest that the serotonergic, adrenergic and dopaminergic control systems markedly differ in ruminants and rodents. The observed differences may be due to differences in the structure of receptors (their amino acid sequence) and the distribution of receptor subtypes (39).…”
Section: Discussionmentioning
confidence: 99%
“…The oesophageal groove is a channel in the medial wall of the reticulo‐rumen of the bovine stomach. The closure of this structure allows the passage of orally administered drugs from the oesophageus directly into the abomasum, preventing the degradation or nonabsorption of certain drugs in the forestomach, and thereby achieving a higher therapeutic efficacy ( cooke & nicholson 1981 ; Van Miert et al . 1998 ) .…”
Section: Introductionmentioning
confidence: 99%